Families' Career Investments and Firms' Promotion Decisions - Frederik Almar; Benjamin Friedrich; Ana Reynoso; Bastian Schulz; Rune Vejlin (CESifo GmbH, 2025)
This paper studies how family and firm investments interact to explain gender gaps in career achievement. Using Danish administrative data, we first document novel evidence of this interaction through a "spousal effect" on firm-side career investments. This effect is accounted for by family labor supply choices that shape worker characteristics, which then influence firms' training and promotion decisions. Our main theoretical contribution is to develop a quantitative life cycle model that captures these family-firm interactions through household formation, families' joint career and fertility choices, and firms' managerial training and promotion decisions. We then use the estimated model to show that the interaction between families and firms in the joint equilibrium of labor and marriage markets is important when evaluating firm-side and family-side policy interventions. We find that gender-equal parental leave and a managerial quota can both improve gender equality, but leave implies costly skill depreciation, whereas the quota raises aggregate welfare, in part through adjustments in marital sorting towards families that invest in women.
Keywords: 330; gender inequality; career investments; firm training; management promotions; marriage market matching